O acesso à saúde das mulheres privadas de liberdade no sistema carcerário da Paraíba - Alves, Rayanne Santos (2020)
INTRODUCTION: The Access of the prison population to comprehensive health care in the Unified Health System is defined by the National Policy of Comprehensive Care for Persons Deprived of Liberty in the Prison System, which emphasizes the guarantee of the right to health of Persons Deprived of Liberty, confined in prison establishments, which makes minimizing the differences between intramural and extramural life essential for reducing inequities and universal access to health. This policy highlights complementary actions aimed at the prison population, governed by respect for human rights and social justice. Women prisoners are very vulnerable to illness, as the precarious conditions of the prisons and the deprivation of freedom itself interfere in maintaining health. OBJECTIVE: To understand the relationship between the quality of access to health for women deprived of liberty in the prison system in Paraíba and their attributes, as well as how psychosocial problems have affected this public. METHODOLOGY: This is a descriptive, exploratory study with a quantitative and qualitative approach. The study subjects were composed of 178 women deprived of their liberty in the Paraíba prison system, in a closed regime. To treat the information collected from 16 interviews; carried out using a qualitative approach, the software Interface de R pourles Analyses Multidimensionneles de Textes et de Questionnaires (IRAMUTEQ) was used to support the analysis of the statements. For data analysis, descriptive statistics of the data were made and then the statistical model for decision making was applied: Ordinal Logistic Regression. RESULTS: Incarcerated women in Paraíba have access to health, but the quality for them (74,7%) is characterized as having little and moderate access. The attributes Time and Type of Crime influence the quality of access to health, as they obtained statistically significant data: prison time equal to or greater than 2 years has a 35% more chance of having more access to health; as well as inmates who not committed crimes related to trafficking or fraud are 62% more likely to have access to health care than inmates who have committed such crimes. With the application of the Hospital Scale for Anxiety and Depression (HADS), 74,2% anxiety and 69,1% depression out of the 178 study participants. With analysis of the content of the interviews with participants, weaknesses in access to health are observed regarding: quality of care and quantity of health professional; medications, exams and testes available to the prisoners; needs in meeting demands in non-urgent cases and health activities. CONCLUSION: The prison health services provides access to health care for women prisoners, but greater investment in human resources, health activities, non-urgent care and the organization of the flow of health care is necessary for this access to be of higher quality, since the deprivation of freedom increases the vulnerability to physical and mental illness.